2007
DOI: 10.1016/s1726-4901(08)70038-8
|View full text |Cite
|
Sign up to set email alerts
|

Main Pulmonary Artery Aneurysm

Abstract: Pulmonary artery aneurysm is a rare lesion of the thoracic cavity. Different etiologies have been reviewed, but idiopathic lesions without other symptoms are seldom reported. Usually, surgical interventions are suggested, but the long-term outcomes are not well established. Here, we report a 24-year-old man with main pulmonary artery aneurysm who successfully underwent aneurysmectomy and polytetrafluoroethylene vascular graft replacement. The postoperative course was uneventful, and the following image study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 10 publications
0
48
0
1
Order By: Relevance
“…[34][35][36] Greene and Baldwin 37 have defined 4 pathological criteria for an idiopathic PAA: simple dilatation of the pulmonary trunk with or without involvement of the rest of the arterial tree, the absence of intracardiac or extracardiac shunts, the absence of chronic cardiac or pulmonary disease, and the absence of arterial disease such as syphilis or more than minimal atheromatosis or arteriosclerosis of the pulmonary vascular tree.…”
Section: Idiopathicmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] Greene and Baldwin 37 have defined 4 pathological criteria for an idiopathic PAA: simple dilatation of the pulmonary trunk with or without involvement of the rest of the arterial tree, the absence of intracardiac or extracardiac shunts, the absence of chronic cardiac or pulmonary disease, and the absence of arterial disease such as syphilis or more than minimal atheromatosis or arteriosclerosis of the pulmonary vascular tree.…”
Section: Idiopathicmentioning
confidence: 99%
“…9,20,34 Clinical symptoms include dyspnea, chest pain, hoarseness, palpitation, and syncopal episodes. 6,14,20,21,[34][35][36] Bronchus compression by a large PAA may be responsible for cyanosis, cough, and increasing dyspnea, pneumonia, fever, and bronchiectasis. 20,21,28,34,35,39 In addition, patients with PAA have a high incidence of pulmonary emboli.…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…The aneurysms in the main pulmonary artery and its two branches are classified as PAA [2]. In autopsy studies the PAA frequency was found to be 1:14000 [1].…”
Section: Discussionmentioning
confidence: 99%
“…Veldtman et al suggested that in low pressure aneurysms, the timing for surgery depends on the size and function of the right ventricle (related to pulmonary stenosis or insufficiency) rather than the size of the aneurysm [1]. Considering the size of the aneurysm and the possibility of anticoagulation, the patient was referred to pneumonology, rheumatology and cardiovascular surgery for further evaluation and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation